Microencapsulated Oregano Essential Oil as a Natural Preservative of Beef Burger during Refrigerated Storage - Fathy M. Mehaya; Salah H. Salem; Ayman A. Mohammad; Heba M. Amer; Wenyi Kang (Journal of Food Quality)
Meat products are highly perishable and prone to deterioration, which poses potential health hazards. This research aims to assess the efficacy of encapsulated oregano essential oil (EOEO) as a natural preservative agent to maintain the chemical and microbiological quality of beef burgers during refrigerated storage. Hydrodistillation was used to extract OEO from oregano. The encapsulation of OEO using a combination of biopolymers (maltodextrin, gum arabic, and whey protein) provides high encapsulation efficiency (89.1%). Both crude and encapsulated OEOs were analyzed for their chemical constituents and antimicrobial activity. Encapsulated OEO, at levels of 0.25%, 0.5%, 0.75%, and 1%, was incorporated during the beef burger processing. Microbiological and chemical parameters were assessed every 4 days over a 16-day storage period. GC-MS results revealed that carvacrol (70 and 79.31%) and p-cymene (11.56% and 9.05%) dominated the crude and encapsulated OEOs, respectively. Both forms of OEO exhibited potent antimicrobial activity, with encapsulation further enhancing this property. The incorporation of EOEO into burger samples reduced the total microbial count. Subsequently, it decreased the formation of total volatile nitrogen (TVN), trimethylamine (TMA), thiobarbituric acid (TBA), and biogenic amines (BAs) during storage. Addition of EOEO at the level of 1% retarded the formation of BAs, TVN, TMA, and TBA in burger samples by 72.8%, 43.23, 42.07, and 44.44%, respectively, compared to the control sample after 16 days of storage. Principal component analysis (PCA) was applied to establish correlations between microbiological and biochemical markers of beef burgers. The PCA results show that PC1 (89.81%) and PC2 (7.25%) can explain more than 97% of the variability in the dataset. The results support the potency of EOEO as an effective and safe preservative agent to maintain the safety and quality of beef burgers during storage.